Institutions, bargaining power and labor shares - Benjamin Bental; Dominique M. Demougin (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
We use a static framework characterized by both moral hazard and holdup problems. In the model the optimal allocation of bargaining power balances these frictions. We examine the impact of improved monitoring on that optimal allocation and its impact upon effort, investment, profits and rents. The model's predictions are consistent with the recent evolution of labor shares, wages per efficiency units and the ratio of labor in efficiency units to capital in several OECD countries. The model suggests further that improvement in monitoring may also play a key role in understanding opposition to institutional reforms in the labor market.
Keywords: D02; D24; 330; moral hazard; hold up; bargaining; labor share